Development of the Soekarno–Hatta International Airport Rail Link Project Using the Value Engineering Method: Creating Value for Money - Berawi, Mohammed Ali; Susantono, Bambang; Dikun, Suyono; Ilyas, Tommy; Rahman, Herawati Zetha; Berawi, Abdur Rohim Boy; Zagloel, Teuku Yuri; Miraj, Perdana; Petroceany, Jade Sjafrecia (UI Scholars Hub, 2014)
Soekarno–Hatta Airport is the main gateway for international flights to Greater Jakarta. Its accessibility depends on the inter-city and Sedyatmo toll roads, which causes congestion in peak hours, leading to uncertainty about travel times. The Soekarno–Hatta International Airport Rail Link (SHIARL) is proposed as an alternative mass transportation project, which is expected to provide accessibility and mobility for people and goods to and from the airport. Previously, the project was unattractive to private investors as it was technically and financially unfeasible. Therefore, this research aims to improve the feasibility of the Soekarno-Hatta International Airport Rail Link (SHIARL) by using a value-engineering approach to create maximum value for money for the project. This research combines quantitative and qualitative methods. Questionnaire surveys are distributed to various stakeholders in the project, and a focus-group discussion (FGD) is conducted. The results identified additional, innovative functions through the integration of the Mass Rapid Transit (MRT), flood control, telecommunications, and development in the downtown area around the station. The life-cycle cost analysis confirmed the increased value for money because of the project’s additional functions, including a positive Net Present Value (NPV). Moreover, the findings showed that the internal rate of return (IRR) was 3% higher than the original single-function project.